Позасловникова лексика у прозі Ліни Костенко (на матеріалі роману «Записки українського самашедшого», К., 2010): словникові матеріали - Балог, В. (Лексикографічний бюлетень, 2012)
Article is devoted to the lexical-semantic analysis of new words in Lina Kostenko’s prose novel «Memoirs of Ukrainian crazy» (Записки українського самашедшого) (K., 2010). Contextual fields, character of nominations has been analyzed and monolingual dictionary entries for the neologisms and neosemantisms of common language has been proposed based on the material of new words and meanings, collected by continuous sampling.